2013
DOI: 10.1371/journal.pone.0064816
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of KRAS Mutations in Advanced Non-Small Cell Lung Cancer

Abstract: Clinical implications of KRAS mutations in advanced non-small cell lung cancer remain unclear. We retrospectively evaluated the prognostic and predictive value of KRAS mutations in patients with advanced NSCLC. Among 484 patients with available results for both KRAS and EGFR mutations, 39 (8%) had KRAS and 182 (38%) EGFR mutations, with two cases having both mutations. The median overall survivals for patients with KRAS mutations, EGFR mutations, or both wild types were 7.7, 38.0, and 15.0 months, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 30 publications
6
78
4
1
Order By: Relevance
“…Although the issue of KRAS mutations in lung cancer is controversial, a recent study of 484 patients found that they are significantly associated with shorter survival in advanced NSCLC (OS of 7.7 for patients with the G12C mutation vs. 15.0 months for those KRAS wt; ref. 24). In the present study, the prognostic value of TP53 nondisruptive mutations was not dependent on EGFR or KRAS status, and was observed both in chemotherapy-treated, EGFR-wt patients as well as in EGFR-mut patients treated in first line with erlotinib or chemotherapy.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although the issue of KRAS mutations in lung cancer is controversial, a recent study of 484 patients found that they are significantly associated with shorter survival in advanced NSCLC (OS of 7.7 for patients with the G12C mutation vs. 15.0 months for those KRAS wt; ref. 24). In the present study, the prognostic value of TP53 nondisruptive mutations was not dependent on EGFR or KRAS status, and was observed both in chemotherapy-treated, EGFR-wt patients as well as in EGFR-mut patients treated in first line with erlotinib or chemotherapy.…”
Section: Discussionsupporting
confidence: 57%
“…Two recent reports have shown that KRAS mutations are associated with shorter survival in chemotherapy-treated advanced NSCLC (24,25). Therefore, samples were analyzed for KRAS mutations (exons 12-13).…”
Section: Resultsmentioning
confidence: 99%
“…A recent analysis also demonstrated that the amount of KRAS mutations detected using a sensitive PCR-based assay may correlate with the efficacy of anti-EGFR therapy in patients with human colorectal cancer (31). Similarly, in pancreatic cancer, KRAS mutations (codon 12 or 13) are associated with worse prognosis (32), and in NSCLC, patients with advanced KRAS-mutant cancer have a shorter survival compared with those with EGFR-mutant or EGFR/KRAS wild-type (WT) cancers (33,34). In addition, KRAS mutations predict for resistance to treatment with EGFR tyrosine kinase inhibitors (17,35,36).…”
Section: Clinical-translational Advancesmentioning
confidence: 97%
“…In the LACE-BIO collaborative group study, patients harbouring codon 13 mutations experienced much worse outcomes when allocated to the chemotherapy group compared to the observation arm (HR 5.78, 95% CI 2.06-16.22; p<0.001, interaction=0.002), suggesting a deleterious effect of adjuvant chemotherapy in this subgroup of patients [14]. In KRAS-mutant NSCLC, type of chemotherapy regimen seems to lead to similar clinical outcomes [17,18]. Until 2010, KRAS mutations were considered negative predictive factors in advanced NSCLC patients treated by inhibitors of the tyrosine kinase domain (TKI) of the EGFR, according to the results of two meta-analyses evaluating both erlotinib and gefitinib [5,19,20].…”
mentioning
confidence: 99%